Four-dimensional in situ imaging of chemical membrane degradation in fuel cells. (1st June 2021) - Ramani, D.; Singh, Y.; White, R.T.; Haddow, T.; Wegener, M.; Orfino, F.P.; Ghassemzadeh, L.; Dutta, M.; Kjeang, E.
Highlights: Chemical membrane degradation is tracked using 4D in situ XCT visualization. Microstructural observations are correlated to fuel cell performance parameters. Membrane thinning and electrode shorting are identified as key drivers of failure. Degradation is more severe under lands than under channels. Abstract: Chemical membrane degradation is considered a key impeding issue for durability of polymer electrolyte fuel cells. Chemical additives have been developed to mitigate this phenomenon by preventing radical attack and associated membrane thinning. In this work, a 4D in situ X-ray visualization approach is adopted to examine the pure chemical degradation effects of non-reinforced, mechanically reinforced, and mechanically and chemically reinforced fuel cell membranes. The 4D approach is achieved by non-invasive, identical location 3D (x, y, z) imaging of the fuel cell at different lifetime stages (t). Observations show that local membrane thinning culminating in electrode-shorting under land regions is the key failure mode for non-reinforced and mechanically reinforced membranes without chemical additives. The ePTFE layer within the mechanically reinforced membrane does not prevent electrode shorts and exhibits divot formation. Preferential shorts under the land regions show that mechanical stresses due to clamping pressure can accelerate electrode shorting at advanced stages of chemical degradation. In contrast, the mechanically and chemically reinforced membrane sustains significantly longer test duration without failure and significant membrane thinning, highlighting the radical scavenging effect. No membrane pinhole or crack development is observed in any of the three membranes, suggesting that such failures require additional mechanical degradation. Graphical abstract: Image, graphical abstract